(untitled) (Estudos em Design, 2019)
The theoretical writing by textile designer and artist, Anni Albers, in her self-authored books On Designing (1961) and On Weaving (1965) provide artists and designers with insights and methods for stimulating resourceful and creative ingenuity. This article examines Albers’ modernist theories as they are enacted upon through material and process in a quest to apply Anni Albers’ theories as a methodology for practice-led research. While teaching at Black Mountain College from 1933–1949, Albers encouraged her students to begin their creative process by “starting at zero” (Fesci, 1968) therefore this research begins in the same way. Anxieties that arise from making without knowing what something is or what that something may become must be put aside. Trust in the process becomes paramount as creative explorations start from a place of intuitive making which leads the practitioner to more structured and purposeful research leading to new ideas and foresight into future projects. Keywords: Anni Albers, practice-led research, materials, process, methodology